Travels from paper to the screen, to the web, to music Intermediality and Children's and Y. A. Literature - Pérez, Soledad (2017)
The present contribution aims at creating awareness of a fairly recent field of study that, among many things, can be used in language classes as an alternative way of dealing with storytelling: Intermediality. I shall present definitions, concepts and examples in order to help teachers comprehend, question and reflect upon a phenomenon which is gaining relevance in our -and students’- daily lives, as well as in classrooms; and how it can allow a more innovative approach to teaching. Our focus is on Children’s and Young Adult’s Literature. As we shall see, this is not a completely new trend, but it is growing more and more inventive, and new ways of ‘consuming’ stories -and new ways of telling themkeep appearing.